Videogames and logical mathematical ability: the Game-Over project - Liliana D'Angelo (Firenze University Press, 2017)
Focus of this paper is the possibility to broaden the learning experience by using videogames to promote a "learning by doing" methodology.Purpose of the "Game-Over" project was in fact giving, through designing and implementation of a videogame, valuable educational experiences simulating interactive learning scenarios, aiming to improve students' problem solving skills.   Videogiochi e abilità logico-matematiche: il progetto Game-Over Oggetto del presente articolo è l'ampliamento dell'esperienza didattica attraverso l'utilizzo dei videogiochi come mezzo per promuovere l'apprendimento attivo (learning by doing). Con il progetto "Game-Over" ci si è posti l'obiettivo di fornire, attraverso l'ideazione e la creazione di un videogioco, esperienze formative significative che simulano scenari di apprendimento interattivi, allo scopo di migliorare le competenze di problem-solving degli studenti